Increase of carbapenem-resistant Acinetobacter baumannii infection in acute care hospitals in Taiwan: association with hospital antimicrobial usage. - Chiu-Hsia Su (Public Library of Science (PLoS), 2012)
Objective Carbapenem-resistant Acinetobacter baumannii (CRAB) has emerged as an important pathogen causing healthcare-associated infections (HAIs) in Taiwan. The present study is aimed to investigate the epidemiology of HAIs caused by CRAB and the association of CRAB infection and hospital usage of different antimicrobials. Methods Two nationwide databases in the period 2003 to 2008, the Taiwan Nosocomial Infection Surveillance System and National Health Insurance claim data, were used for analysis. A total of 13,811 healthcare-associated A. baumannii infections and antimicrobial usage data from 121 hospitals were analyzed. Results There was a significant increase in the proportion of number of HAIs caused by CRAB over that by all A. baumannii (CRABpAB), from 14% in 2003 to 46% in 2008 (P<0.0001). The greatest increase was in central Taiwan, from 4% in 2003 to 62% in 2008 (P<0.0001). Use of anti-pseudomonal carbapenems, but not other classes of antibiotics, was significantly correlated with the increase of CRABpAB (r = 0.86, P<0.0001). Conclusions We suggested that dedicated use of anti-pseudomonal carbapenems would be an important intervention to control the increase of CRABpAB.